Evaluation of Drug Prescription Pattern using World Health Organisation Prescribing Indicators in a Tertiary Care Hospital, Bangalore - Cherian, Ritty Sara; Stuthy, Gaddam Mrudula; Salin, Dhanush (Journal of Drug Delivery and Therapeutics, 2021)
Aim of the study: To monitor the drug use patterns by using WHO prescribing indicators in a tertiary care hospital and to minimise the irrational prescribing practices by the prescribers. To monitor the drug use patterns by using WHO prescribing indicators in a tertiary care hospital and to minimise the irrational prescribing practices by the prescribers. Materials and Methods: This is a prospective observational study, the patients who were satisfying the inclusion criteria will be enrolled into the study. The patient’s data were collected in specially designed documentation form. The collected data’s were assessed using descriptive statistics. Results: The study was conducted in 143 patients in which the average number of drugs per encounters was 3.5 and the percentage of drugs in the generic name was 37.10% (n=190), and in brand names were 62.89% (n=322). The number of encounters with antibiotics was 61.5% and where as 57.35% of the total drugs prescribed was injections. Most of the medicines prescribed were included in the list of essential medicines of India that is 96.09% and without use of antibiotics 38.46% (n=55). Conclusion: Poly pharmacy leads to drug chances of interactions and risk of ADRs and revealed that most of the patients were prescribed with the poly pharmacy and in brand names. The use of antibiotics was much more in the study, which should be minimize so that antimicrobial resistance can be minimized. Keywords: adverse drug reaction, essential drug list, prescribing indicators